Practice Variations in the Diagnosis and Treatment of Pulmonary Embolism - Devesh Thakkar; Frances Garden; John Nguyen; Brenda Ta; Sikandar Hussaini; Claudia C. Dobler (Pulmonary Medicine)
Venous thromboembolism is responsible for a significant burden of disease worldwide. Despite the publication of multiple international guidelines, anecdotal evidence suggests significant clinical variation exists in the diagnostic and management pathways of pulmonary embolism (PE). We conducted a retrospective cohort study using electronic medical records to examine clinical variation in patients admitted to a tertiary referral center in Australia with a diagnosis of PE between November 2018 and January 2020. Three hundred cases met the inclusion criteria; we found variation in rates of compression ultrasonography, acute investigation of the right ventricle, and planning of repeat imaging at specialist follow-up. Guidelines do not address the use of compression ultrasonography in already diagnosed PE, are conflicting in their recommendation for acute investigation of the right ventricle, and recommend repeat imaging only if there are persistent symptoms at the time of specialist follow-up. The variations we found in this study may in part be due to physician preference or due to the paucity of evidence for some of these diagnostic practices. Robust future studies are required to guide the use of these investigations in PE.